Relationship between 25-hydroxyvitamin D and IGF1: a cross-sectional study of the Third National Health and Nutrition Examination Survey participants - Wei Li; Tao Yu (BMC, 2023)
Abstract Background 25-Hydroxyvitamin D (25OHD) and insulin-like growth factor 1 (IGF1) are crucial for bone health. Some studies have shown that they interact, whereas others have indicated no association. However, it remains inconclusive whether the interaction between the two is dose dependent. Herein, we explored the relationship between 25OHD and IGF1 by conducting a cross-sectional study. Methods This study involved 6,046 individuals from the Third National Health and Nutrition Examination Survey (NHANES III). The dependent and independent variables were IGF1 and 25OHD levels, respectively. The covariates included age, sex, race, BMI, exercise, smoking behavior, alcohol intake, diabetes, and serum calcium level. Multiple linear regression and generalized additive model were employed to analyze the relationship between 25OHD and IGF1. Interaction and hierarchical analyses were also performed. Results The 25OHD and IGF1 levels positively correlated after adjusting for covariates (β = 0.16, 95% CI: 0.04-0.29, P = 0.0103). Smooth curve fitting demonstrated a curvilinear relationship. When the 25OHD level was < 75 nmol/L, a positive correlation (β = 0.43, 95% CI: 0.25-0.62, P < 0.0001) was observed. When the 25OHD level was > 75 nmol/L, a negative correlation was observed (β = −0.53, 95% CI: −0.90 to −0.15, P = 0.0057). Conclusion This study demonstrated a nonlinear relationship between 25OHD and IGF1. It suggests that keeping the 25OHD level within a specific range may be more conducive to bone health. Additionally, when IGF1 is used to evaluate the efficacy and safety of recombinant human growth hormone (rhGH) in growth hormone deficiency treatment, the effect of 25OHD on the actual IGF1 level should be taken into account.